2022
DOI: 10.3390/diagnostics12112810
|View full text |Cite
|
Sign up to set email alerts
|

Placental and Umbilical Cord Anomalies Diagnosed by Two- and Three-Dimensional Ultrasound

Abstract: The aim of this review is to present a wide spectrum of placental and umbilical cord pathologies affecting the pregnancy. Placental and umbilical cord anomalies are highly associated with high-risk pregnancies and may jeopardize fetal well-being in utero as well as causing a predisposition towards poor perinatal outcome with increased fetal and neonatal mortality and morbidity. The permanent, computerized perinatology databases of different international centers have been searched and investigated to fulfil th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Several studies have reported that fetuses with UCC were later complicated with UC hematomas during pregnancy, leading to fetal demises 51,52 . UC hemangioma also can increase fetal mortality mainly by compressing, developing thrombosis, or rupturing 16 . In the authors' hospital, there was also a case of UC hemangioma, where the umbilical vein dilated and formed umbilical cyst–like changes, finally forming UC thrombosis, and then contributing to intrauterine fetal death.…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…Several studies have reported that fetuses with UCC were later complicated with UC hematomas during pregnancy, leading to fetal demises 51,52 . UC hemangioma also can increase fetal mortality mainly by compressing, developing thrombosis, or rupturing 16 . In the authors' hospital, there was also a case of UC hemangioma, where the umbilical vein dilated and formed umbilical cyst–like changes, finally forming UC thrombosis, and then contributing to intrauterine fetal death.…”
Section: Methodsmentioning
confidence: 81%
“…Amniotic inclusion body cysts refer to the amniotic epithelium wrapped in the UC during its formation 14 . UC tumors are rare, most of which are hemangiomas, and can be manifested as UCC under ultrasound examination 15,16 . Color Doppler ultrasound helps to identify vascular structures of cysts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Ultrasound performed by an experienced operator has a sensitivity and specificity of up to 90% in gray-scale mode, and sonographic markers associated with PAS are multiple vascular lacunae, loss of the normal hypoechoic retroplacental zone in the myometrium, abnormality of the myometrium, abnormality of the uterine serosa-bladder interface, thinning of the retroplacental myometrium, and bulging of the lower uterine segment. 31 The main 2D ultrasound signs suggestive of PAS are the follows:…”
mentioning
confidence: 99%